Unlocking the power of social media marketing: Investigating the role of posting, interaction, and monitoring capabilities in building brand equity - Sofiane Laradi; Noureddine Berber; Hafiz Mudassir Rehman; Md Billal Hossain; Lee-Chea Hiew; Csaba Bálint Illés (Cogent Business & Management, 2023)
Given the extensive utilisation of social media, brands have grown increasingly dependent on it to build brand equity. As a result, acquiring specific capabilities in the realm of digital marketing has become a necessity. This research aims to investigate the essence of Social Media Marketing Capabilities (SMMC) and assess the forecasting of its capability on Consumer-Based Brand Equity using qualitative and quantitative research methods. The results demonstrate that the ability to post and interact on social media positively correlates with consumer-based brand equity. Conversely, the monitoring capabilities of social media marketing (SMM) did not establish a significant association with Consumer-Based Brand Equity. These findings have important implications for marketing, branding, and community management professionals who can leverage these insights to optimise their social media strategies and maximise their returns by focusing on enhancing specific SMM capabilities.
Keywords: 650; brand image; capabilities theory; consumer-based brand equity; digital marketing; Social Media Marketing Capabilities (SMMC)